Advanced monoenergetic reconstruction technique in dual-energy computed tomography for evaluation of vascular anatomy before adrenal vein sampling. (February 2020) - Nakayama, Keita; Shimohira, Masashi; Nakagawa, Motoo; Ozawa, Yoshiyuki; Sawada, Yusuke; Ohta, Kengo; Ohashi, Kazuya; Shibamoto, Yuta
Background: In adrenal vein sampling, selecting the right adrenal vein is technically difficult and it is important to evaluate the right adrenal vein anatomy before adrenal vein sampling. The advanced monoenergetic reconstruction technique has recently become available and we hypothesized that this technique may be useful. Purpose: To evaluate the usefulness of the advanced monoenergetic reconstruction technique in dual-energy computed tomography (CT; advanced monoenergetic images) for evaluation of vascular anatomy before adrenal vein sampling. Material and Methods: Twenty-one patients underwent three-phase (20, 30, and 70 s) contrast-enhanced CT before adrenal vein sampling. Advanced monoenergetic images were reconstructed at 40 keV and analyzed objectively and subjectively in comparison with the standard 120-kVp images. As objective evaluation, the signal-to-noise ratio and contrast-to-noise ratio of the right adrenal vein were assessed. As subjective evaluation, two radiologists assessed the delineation of the right adrenal vein using a 5-point Likert scale (1 = poor, 5 = excellent). Furthermore, the technical success rate of adrenal vein sampling and procedure time were also evaluated. Results: There was no difference in the signal-to-noise ratio between the two groups. The contrast-to-noise ratios of the right adrenal vein of advanced monoenergetic images were higher than those of the standard images ( P  < 0.05). The Likert scores of advanced monoenergetic images were higher than those of the standard images ( P  < 0.05). The technical success rate of adrenal vein sampling was 95% (20/21) and the median of procedure time was 103 min (range = 59–197 min). Conclusion: Advanced monoenergetic imaging appears to be useful in the delineation of the right adrenal vein before adrenal vein sampling.